If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8x + 7 + 2x = 19 Reorder the terms: 7 + -8x + 2x = 19 Combine like terms: -8x + 2x = -6x 7 + -6x = 19 Solving 7 + -6x = 19 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -6x = 19 + -7 Combine like terms: 7 + -7 = 0 0 + -6x = 19 + -7 -6x = 19 + -7 Combine like terms: 19 + -7 = 12 -6x = 12 Divide each side by '-6'. x = -2 Simplifying x = -2
| y=9-21 | | 5=4(x-3) | | 3x=11x+6 | | x=9x+4 | | 12x+10+x+40=180 | | 5z+4=-2z+25 | | -5x=8x+21 | | 8r=2 | | 3(f+2)+9-5f=14 | | 12x^2-336=0 | | 12(t+7)=48 | | -2x=6x-24 | | (x^2-3x+4)-(x^2+2x+5)=0 | | 13x-6x=56 | | 8z+25=7z+6 | | 10x-2=6x+16 | | 5p+10=8p+1 | | 2(x-3)=14x | | x^3-10x=-3x^2+24 | | 4z/9-9=5 | | 2q+3+q+9= | | Q=20-(2p) | | 8n^2-n-1= | | 4+x=2x+12 | | 2 = f4– 1 | | -9x+18=-3 | | x^2+xy+y^2=14 | | -83=-2(-6v-3)+7 | | 10+2f=16 | | 2=4-2t | | s^2-5s+9=0 | | -13x+-6=59 |